WATCHING INDIAN MOVIES IN AUSTRALIA - Adrian Athique (South Asian Popular Culture Vol. 3, No. 2, October 2005, pp. 117-133, 2005)
This article draws on a body of interviews conducted during 2003-04 with movie-viewers, distributors and exhibitors of Indian movies in Australia, primarily in the Sydney region of New South Wales. My immediate concern is with the manner in which Indian movies reach an audience in Australia and how that audience is described, both by themselves and by those who seek to cater to them. The wider context of this study is its contribution to a transnational perspective on Indian movies and the cultural understandings that they generate within and across specific localities. As such, this article attempts to reformulate the conception of media-communities by replacing an ethnographic model with an emphasis on surveying the diverse inhabitants of a `cultural field' constructed around the Indian movie.